The Maritime Dimension of International Security - Chalk, Peter (RAND Corporation, 2023)
The vast size and highly unregulated nature of the world's waterways havemade the maritime environment an increasingly attractive theater forperpetrators of transnational violence. Piracy and sea-borne terrorism havebeen on the rise since 2000. While the United States has spearheaded severalimportant initiatives to improve maritime security, the author urgespolicymakers to consider four additional measures to safeguard the world'soceans.